Penerapan Larangan Berpoligami Bagi Anggota Polri Berdasarkan Peraturan Kepolisian Negara Republik Indonesia Nomor 6 Tahun 2018 - Sudiyanto; Eddy Asnawi; Bahrun Azmi (UIR Law Review, 2022)
The disciplinary regulations for Polri members are a series of norms to foster, uphold discipline and maintain order in the life of Polri members. It is necessary to instill in every member of the Police the awareness that discipline is honor. Discipline of members of the Police is an honor as a member of the Police that shows credibility and commitment as a member of the Police. While the legal consequences if a police officer who carries out a polygamous marriage without permission is caught either by his wife or another party and reported to his superiors, the police officer will be subject to sanctions in accordance with the rules that apply to each member of the police as outlined in the police code of ethics. The purpose of this study is to analyze the Implementation of the Prohibition of Polygamy for Members of the Indonesian National Police Based on the Regulation of the Chief of Police Number 6 of 2018, and to analyze the Obstacles and Efforts in Implementing the Prohibition of Polygamy f Keywords: Application, Polygamy, Police